Determination of the total soluble nitrogen content of malt and beer by the Dumas combustion method: collaborative trial: Submitted on behalf of the Analysis Committee of the Institute of Brewing and the Analysis Committee of the European Brewery Convention - Johnson, B. A.; Johansson, C.-G. (BrewingScience, 2000)
The determination of the total soluble nitrogen content of malt and beer, by the Dumas procedure, has jointly been collaborativelytested by the Analysis Committees of the Institute of Brewing (IOB) and the European Brewery Convention (EBC).Five samples of beer (range 362 to 1159 mg/l) and five samples of malt (range EBC 0.598 to 0.798% m/m (dry basis) andIOB 0.534 to 0.706% m/m (dry basis)) were distributed to eighteen participating laboratories for analysis. Precision valueswere judged to be independent of the mean soluble nitrogen content for malt by both IOB and EBC methodologies. Valuesfor r₉₅ and R₉₅ were 0.047 and 0.136%m/m for EBC laboratory wort and 0.039 and 0.144% m/m for IOB laboratory wortrespectively. Precision values for beer were judged to be dependent upon the mean nitrogen content (m) in the case of r₉₅and independent of the mean nitrogen content in the case of R₉₅. Values for r₉₅ and R₉₅ were 0.074m and 120 mg/l respectively.